[Haskell-beginners] Monad for Pair
Marcin Mrotek
marcin.jan.mrotek at gmail.com
Wed Nov 18 08:28:22 UTC 2015
> You might want to try writing out a test instance in full and re-checking the second law.
Ok, while the part upto Applicative is correct and unambiguous:
data Pair a = Pair a a
instance Functor Pair where
fmap f (Pair a b) = Pair (f a) (f b)
instance Applicative Pair where
pure a = Pair a a
Pair fa fb <*> Pair a b = Pair (fa a) (fb b)
there are at least two implementations of Monad (assuming return=pure,
also GHC 7.10 allows omitting return and implements it exactly like
that):
-- implementation (a)
instance Monad Pair where
Pair a _ >>= k = k a
-- implementation (b)
instance Monad Pair where
Pair _ b >>= k = k b
... neither of which can satisfy the laws. There are more:
-- implementation (c)
instance Monad Pair where
Pair a b >>= k = Pair a' b'
where
Pair a' _ = k a
Pair _ b' = k b
-- implementation (d)
instance Monad Pair where
Pair a b >>= k = Pair a' b'
where
Pair _ b' = k a
Pair a' _ = k b
and, well:
instance Monad Pair where
Pair a b >>= _ = Pair a b
Did I miss anything? Now, trying to get the second law to work:
a) m >>= return = m
Pair a b >>= (\a -> Pair a a) = Pair a b
Pair a a = Pair a b
contradiction.
b) m >>= return = m
Pair a b >>= (\a -> Pair a a) = Pair a b
Pair b b = Pair a b
contradiction.
c) m >>= return = m
Pair a b >>= (\a -> Pair a a) = Pair a b
Pair a b = Pair a b
no contradiction this time, I'll write the other laws after I'm done
with the second for the other instances.
d) m >>= return = m
Pair a b >>= (\a -> Pair a a) = Pair a b
Pair b a = Pair a b
contradiction.
e) m >>= return = m
trivially correct.
Testing the first law for (c) and (e) that passed the second law:
c) return a >>= k = k a
Pair a a >>= k a = k a
---
Pair a' b' = k a
where
Pair a' _ = k a
Pair _ b' = k a
---
no contradiction again.
e) return a >>= k = k a
return a = k a
contradiction.
Okay, then testing the third law for (c):
m >>= (\x -> k x >>= h) = (m >>= k) >>= h
Pair a b >>= (\x -> k x >>= h) = (Pair a b >>= k) >>= h (*)
Let's again unpack the application of >>= in some pseud-haskell:
Pair a1 _ = (\x -> k x >>= h) a = k a >>= h (**)
Pair _ b1 = (\x -> k x >>= h) b = k b >> =h
Pair a2 _ = k a (***)
Pair _ b2 = k b
plugging it into (*):
Pair a1 b1 = Pair a2 b2 >>= h
Unpacking >>= again:
Pair a3 _ = h a2 (****)
Pair _ b3 = h b2
Pair a1 b1 = Pair a3 b3
Now, testing if a1 = a3, lets bring in (**), (***), and (****):
Pair a1 _ = k a >>= h
Pair a2 _ = k a
Pair a3 _ = h a2
Form the first and the second equations (also using the one for b2
earlier, but it's going to be dropped anyway sooner or later) we get:
Pair a1 _ = Pair a2 b2 >>= h
Unpacking >>= :
Pair a4 _ = h a2
Pair _ b4 = h b2
But from the third equation we know that (Pair a3 _ = h a2) so:
Pair a1 _ = Pair a3 _
This does seem to work, I have no idea why. I'm pretty sure there I've
made a mistake somewhere. Perhaps I shouldn't do equational reasoning
after just getting up, or just use Agda :-/
Best regards,
Marcin Mrotek
More information about the Beginners
mailing list